2008
DOI: 10.1210/en.2008-0564
|View full text |Cite
|
Sign up to set email alerts
|

Cold Tolerance in Hypothyroid Rabbits: Role of Skeletal Muscle Mitochondria and Sarcoplasmic Reticulum Ca2+ ATPase Isoform 1 Heat Production

Abstract: Brown adipose tissue (BAT) is involved in rat and mice thermoregulation, and heat produced by BAT depends on the concerted action of thyroid hormones and catecholamines. Little is known about cold-induced thermogenesis in mammals that have little or no BAT, such as rabbits. In these animals, thermogenesis primarily occurs in skeletal muscle. In this work, we have studied the effect of cold acclimation (4 C for 10 d) in normal and hypothyroid rabbits. It is known that hypothyroid rats die after a few hours of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 46 publications
4
58
0
Order By: Relevance
“…It is for this reason that SERCA1, in addition to being involved in Ca 2+ translocation, has also been related to non-shivering thermogenesis [55]. Conversely, SERCA2, most of the hydrolytic ATP-derived energy, is coupled to Ca 2+ transport to the lumen of the sarcoplasmic reticulum [53]. Recently, we have shown that in skeletal muscle of cachectic tumour-bearing animals, SERCA gene expression and protein content are increased (Fig.…”
Section: Sercamentioning
confidence: 99%
See 2 more Smart Citations
“…It is for this reason that SERCA1, in addition to being involved in Ca 2+ translocation, has also been related to non-shivering thermogenesis [55]. Conversely, SERCA2, most of the hydrolytic ATP-derived energy, is coupled to Ca 2+ transport to the lumen of the sarcoplasmic reticulum [53]. Recently, we have shown that in skeletal muscle of cachectic tumour-bearing animals, SERCA gene expression and protein content are increased (Fig.…”
Section: Sercamentioning
confidence: 99%
“…Thus, SERCA1 activity may be coupled to Ca 2+ translocation from the cytosol to the sarcoplasmic reticulum, a process that requires a considerable amount of energy since it represents a dynamic process against a concentration gradient. Some of the energy associated with the activity of the pump is released as heat [53]. Interestingly, the pump may also function in an uncoupled way, releasing just heat without translocating Ca 2+ [53,54].…”
Section: Sercamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in an animal model that hypothyroidism promotes an increase in oxygen consumption by skeletal muscle mitochondria and induces an increase in sarcoplasmic reticulum calcium [91]. Thus, hypothyroidism predisposes to statin-induced muscle toxicity and substantially increases the risk of muscle symptoms through the same mechanisms as in "non-thyroid" patients [91].…”
Section: Thyroid Diseases and Statin Intolerancementioning
confidence: 99%
“…In hypothyroid patients, myopathy with mild elevation of serum CK activity is not rare and in a few cases might take the form of overt rhabdomyolysis even in patients not on statin treatment. However, if statin treatment is added it seems that the risk of muscle-related side effects increases markedly [91][92][93][94][95][96][97]. It is therefore recommended that a clinical examination, thyroid-stimulating hormone (TSH) and thyroxine levels measurement should be performed before statin treatment initiation.…”
Section: Thyroid Diseases and Statin Intolerancementioning
confidence: 99%